Negotiating Political Conflicts - Pfetsch, Frank R. (EBL-Schweitzer, 2007)
In an interdependent globalized world negotiation is the only adequate means of finding solutions to political conflicts without resorting to violence; what is negotiation? What are the most important terms and conceptions? What are the relationships between negotiation and its object the conflict? How does the process of negotiation develop? What are the implications of different cultures in international negotiations? What characterizes a durable solution? Empirical examples illustrate theoretical conceptions. Academics and practitioners will find this book an invaluable companion to the the